2003
DOI: 10.1002/humu.10190
|View full text |Cite
|
Sign up to set email alerts
|

TP53 in hematological cancer: Low incidence of mutations with significant clinical relevance

Abstract: Inactivation of the wild‐type p53 gene (TP53) by various genetic alterations is a major event in human tumorigenesis. More than 60% of human primary tumors exhibit a mutation in the p53 gene. Hematological malignancies present a rather low incidence of genetic alterations in this gene (10–20%). Nevertheless, epidemiological studies of the hematological malignancies indicate that the prognosis of patients with a mutation in the p53 gene is worse than those expressing the wild‐type p53 protein. Correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
99
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 61 publications
6
99
0
2
Order By: Relevance
“…Correlations between aberrations of chromosome 17 and mutations of p53 gene have been found during this process and several studies have reported structural alterations of chromosome 17, mutations of p53 gene and p53 protein expression in BP (6)(7)(8)33,34). The reported frequency of p53 alterations in BP of CML is about 30% (33).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Correlations between aberrations of chromosome 17 and mutations of p53 gene have been found during this process and several studies have reported structural alterations of chromosome 17, mutations of p53 gene and p53 protein expression in BP (6)(7)(8)33,34). The reported frequency of p53 alterations in BP of CML is about 30% (33).…”
Section: Discussionmentioning
confidence: 93%
“…p53 mutations are present in less than 5% of children with ALL at initial presentation (7). Mutations were detected more frequently in children with relapsed T-cell ALL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TP53 mutations occur in almost every type of cancer at rates varying between 10% in hematopoietic malignancies [38] and 98% in high-grade serous carcinoma of the ovary [39]. Unlike the majority of tumor suppressor genes, which are inactivated by deletions or truncated mutations, TP53 mostly undergoes missense mutations [40].…”
Section: Discussionmentioning
confidence: 99%